Digital Extramural English, Motivation, and VocabularyAcquisition in English as a Foreign Language Contexts - nina afrida; mauloeddin afna; Nabilah fairuz thifal thifal (Journal of Education and Teaching Learning, 2026)
In the digital era, English learning often extends beyond the classroom as students engage with authentic content via social media, online videos, and games. This study investigates how Informal Digital Learning of English (IDLE) and Extramural English (EE) activities foster vocabulary acquisition and motivation among English education students at IAIN Langsa. The researcher employs a qualitative approach, collecting data through semi-structured interviews and observations. Thematic analysis of the data revealed that learning was driven by audiovisual input, a synergy of intrinsic and ideal L2 self-motivation, and mediated by individual learning styles. Despite the prevalence of these behaviors, formal curricula seldom integrate such informal experiences. This research addresses that gap by examining how digital habits influence vocabulary growth and learner autonomy, which aligns with Indonesia's Merdeka Belajar curriculum and its emphasis on self-directed learning. The findings offer pedagogical insights for bridging formal instruction with informal digital practices, making English education more relevant. Conducted during a critical period of digital transformation, this study provides timely contributions to curriculum development and teacher education, empowering learners to harness their daily digital interactions for lifelong language proficiency.